Oral care practice for the ventilated patients in intensive care units: a pilot survey - Kim Lam Soh; Sazlina Shariff Ghazali; Kim Geok Soh; Rosna Abdul Raman; Sharifah Shafinaz Sharif Abdullah; Swee Leong Ong (Journal of Infection in Developing Countries)
Introduction: Ventilator-associated pneumonia (VAP) is the most common nosocomial infection in intensive care units (ICUs).  One factor causing VAP is aspiration of oral colonisation, which may result from poor oral care practice.  Oral care using tooth brushing can prevent formulation of dental plaque that can be a reservoir for microbes causing VAP.